2010
DOI: 10.1152/ajpregu.00641.2009
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of endothelium-dependent vasodilation in male and female, young and aged offspring born growth restricted

Abstract: Numerous epidemiological studies have shown that cardiovascular dysfunction in adult life may be programmed by compromised growth in utero. Aging is a risk factor for vascular endothelial-dependent dysfunction. After birth, the impact of intrauterine growth restriction (IUGR) on normal aging mechanisms of vascular dysfunction is not known. We hypothesized that IUGR would cause changes in vascular function that would affect the mechanisms of endothelium-dependent vasodilation later in life in an age- or sex-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
94
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(107 citation statements)
references
References 41 publications
10
94
1
2
Order By: Relevance
“…For example, prenatal hypoxia has been shown to reduce NO dependence in vascular tone and promote endothelial-derived hyperpolarization-mediated vasodilation. 20 Whether this shift in vascular control mechanisms by Resv supplementation during development is mediated by hypoxia-related signaling is an intriguing hypothesis, particularly because Resv is known to interfere with hypoxiainducible factor expression and adaptations to hypoxia. 21 In addition to contributing to resting vascular tone, NO has myriad functions, including physiological antagonism of vasoactive mediators, such as ET-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, prenatal hypoxia has been shown to reduce NO dependence in vascular tone and promote endothelial-derived hyperpolarization-mediated vasodilation. 20 Whether this shift in vascular control mechanisms by Resv supplementation during development is mediated by hypoxia-related signaling is an intriguing hypothesis, particularly because Resv is known to interfere with hypoxiainducible factor expression and adaptations to hypoxia. 21 In addition to contributing to resting vascular tone, NO has myriad functions, including physiological antagonism of vasoactive mediators, such as ET-1.…”
Section: Discussionmentioning
confidence: 99%
“…11 We have previously shown that NO modulates cleavage of bET-1 to active ET-1, 22 and this pathway is perturbed in offspring that exhibit a reduced NO-mediated vasodilation. 20,23 We therefore investigated the role of bET-1 conversion to active ET-1 in baseline and l-NAME-induced hypertension in adult offspring. The endothelin-converting enzyme inhibitor CGS attenuated the l-NAME-induced rise in BP, without affecting baseline BP, thus confirming our previous reports that NO tonically inhibits the actions of ET-1, in part by inhibiting the conversion of bET-1 to active ET-1.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Studies such as these have reported that chronic fetal hypoxia can program persistent pulmonary hypertension in the newborn and pulmonary hypertension in the adult offspring. 24 However, because maternal exposure to hypoxia can lead to a significant decrease in maternal food intake, 25 the extent to which any adverse effects on the pulmonary circulation of the offspring are due to under-nutrition and/or under-oxygenation, once again, remain unclear.…”
mentioning
confidence: 99%
“…Пренатальная гипоксия, которая также увеличивает продукцию перекисных агентов, вызывает уменьше-ние у 4-месячных крыс реакции расслабления мезен-териальных сосудов в ответ на действие оксида азота и агентов (метахолина), которые через эндотелий-за-висимые механизмы потенцируют реакции рассла-бления [75]. Интересно, что такой сниженный ответ на оксид азота у нормальных крыс наблюдается толь-ко в пожилом возрасте (18 мес), что подтверждает предположения о том, что оксидативный стресс уско-ряет процессы старения.…”
Section: роль оксидативного стресса как эпигенетического фактораunclassified